AD, Volume 22, n° 2, 1997 - Full Issue - Journal System (Africa Development, 1997)
Contents Facing Donor Missions with Informed Policy Decisions: Lessons from Capacity Strengthening for Policy Analysis in Malawi Suresh C. Babu ....................................5 The Devaluation of the CFA Franc: Some Preliminary Results Jean K. Thisen ................................... 25 Actualité de la pensée économique de Karl Marx et analyse de la crise économique africaine Pana Ewihn-Liba ...............................59 Economic Recovery and Self-sustaining Development in sub-Saharan Africa: A Review of Capacity Building Implications Jide Balogun .....................................69 Preventive Health Strategies and Infant Survival in Zimbabwe Assata Zerai ....................................101 Cameroun : Pourquoi lés noms des grandes figures historiques des années 1950 sont-ils tabous dans la bouche du Président Paul Biya? Wang Sonné ...................................131 Heterodoxy in Political Economy: From an Alternative to the Walrassian Model to a Synthesis with Neo-classical Methodo Hakim Ben Hammouda .................151 Book Review Struggle for the University: A Review Article Paul Tiyam be Zeleza .......................181 A propos de «mouvements ouvriers et crise économique» Réponse à 0. Faye Alfred I. Ndiaye & Bassirou Tidjani ........193 De l'«essai» à la «réponse» de Alfred I. Ndiaye et de Bassirou Tidjani ou les faiblesses d'une pensée connaissante Ousseynou Faye ...................................201 Publications Received and Acquired ......................205